PROFIL DEPOT AIR MINUM ISI ULANG DAN PENERAPAN ANALISIS TOC PADA PEMERIKSAAN KUALITAS AIR MINUM BERDASARKAN SUMBER AIR YANG DIGUNAKAN DI BANDAR LAMPUNG [Profile of drinking water refill depot and application of TOC Analyisis as drinking water quality assessment based on water resources used in Bandar Lampung] - Azhari Rangga; Harun Al Rasyid; neti yuliana; Gilang Muhammad E (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2015)
This study aimed to get a profile of the drinking water refill depots in Bandar Lampung and determined the relationship between total organic carbon (TOC) with the parameters required to analyze drinking water. This study was consisted of two stages. The first stage was a survey, and the second stage was analysis of water samples in the laboratory. The survey form was direct observation in the field and filled a questionnaire which addressed to some places that produce drinking water refill in Bandar Lampung. Laboratory testing was consisted of a sample of the quality testing of physical, chemical, and microbiological properties. Physical quality testing included testing of odor, turbidity, taste, temperature, total dissolved solid (TDS), and color. Chemical quality testing included test of pH, total organic carbon (TOC), inorganic carbon (IC), and total carbon (TC). For the microbiological quality testing included test contamination of total plate count and coliform contamination. Data were analyzed with SPSS program. The results showed that 86% depot of drinking water refill still using standard refining technology that used multiple micro filter and silica sand media filtration and activated carbon, while 14% drinking water refill depot had used reverse osmosis technology. All samples of water from various sources of drinking water refill depots in the city of Bandar Lampung had met the requirements of drinking water quality. The high value of the parameter TOC will be followed by high value of the parameter of pH and color as well, because the parameters of color and pH were positively correlated with TOC parameter.Keywords : drinking water, total organic carbon, water quality.